Pharmacoeconomic study on rivaroxaban vs conventional venous thromboembolism prophylaxis following elective total hip or knee replacement surgery in Serbia: Single centre study - Perović Saša R.; Sikimić Leposava B. (Srpsko lekarsko drustvo, 2017)
Introduction: Venous thromboembolism (VTE) is often clinically unobservable, showing the first symptoms only after the patient has been discharged from the hospital, owing to which symptoms may not be recognized in time and serious complications may arise after hip or knee replacement surgery. The outcome for a patient who has had a symptomatic episode of VTE may be bad due to a risk of recurrent VTE and the development of postthrombotic syndrome. The annual incidence of VTE is around 80-180 cases in 100.000, based on population studies. Worldwide, orthopaedists and anaesthesiologists mostly refer to ACCP guidelines from America, or guidance from NICE and Scottish Medicines Consortium in Europe. All the guidelines include rivaroxaban as a therapy of choice for the prevention of VTE following elective arthroplasty as the therapy with rivaroxaban has shown both effectiveness and cost-savings. Many countries have included rivaroxaban as a medicine of first choice in the therapy for the above described indication. Aim: The objective of this analysis is to demonstrate cost-effectiveness of the new therapy with rivaroxaban versus conventional in VTE prophylaxis for patients undergoing elective hip or knee replacement surgery. Methodology: This paper is a part of the academic IV phase pharmacoecconomic study using extrapolation datas (RECORD 1, RECORD 2, RECORD 3) done in Serbia as single center expirience of Institute for Orthopaedic Surgery 'Banjica', in 2015. Information on drug prices, basic pharmacological characteristics, and on services of health institutions, are taken from the List of Drugs and Pricelist of the Republic Health Insurance Fund, as well as the Thromboembolism Prophylaxis Guide of the Institute 'Banjica'. The Incremental cost-effectiveness ratio (ICER) and Cost-utility analysis (CUA) have also been used in relation to the Quality-adjusted life-year (QALY). Furthermore, in the calculation the proposed price of a defined daily dose (DDD) of rivaroxaban was 3.36 EUR. Results: Total savings obtained annually through the application of rivaroxaban instead of usual prophylaxis (6,900 surgeries) could lead to cost savings of EUR 511,248.35 with the ICER value shows that therapy with rivaroxaban is dominant. Conclusions: The introduction of rivaroxaban in the therapy will enable patients to receive more conformable oral therapy with the same amount of health insurance resources spent, while on the other hand significant savings will be obtained owing to a decrease in the number of inpatient days in hospitals, as well as owing to the fact that regular control examinations of INR and number of blood platelets will not be necessary, which otherwise may amount to EUR 511,248.35annually for the said indication. The authors suggest support for the IV phase of the investigator initiated academic clinical trials with the intention of gaining security and personal experiences of doctors who use rivaroxaban in clinical practice.